UCH-L1 Inhibitor Alleviates Nerve Damage Caused by Moyamoya Disease - Minghua Xu; Xiaomin Zhao; Jiang Zhao; Zhisheng Tan; Chengshi Zhang; Yun Huang; Huiping Zhong; Meifeng Guo; Chen Zhang; Ping Ye; Wentao Zheng (Applied Bionics and Biomechanics)
Background. Moyamoya disease (MMD) leads to nerve injury. Exosomes are touted as bio-shuttles for the delivery of distinct biomolecules inside the cells. Recently, UCH-L1 was shown to play a vital role in nerve injury. However, it is still unknown whether UCH-L1 can improve the nerve injury of MMD. Materials and Methods. Exosomes were isolated from the serum of patients with MMD and healthy controls. The total RNA was extracted from the exosomes, and the level of GFAP and UCH-L1 between the serum exosomes of the two groups was analyzed by a quantitative reverse transcription-polymerase chain reaction and western blot. Exosome labeling and uptake by SH-SY5Y cells were observed by confocal laser microscopy. Cell counting kit-8 assay and flow cytometry were used to determine the viability and apoptosis of SH-SY5Y cells, respectively. Results. Exosomes were successfully isolated and identified from serum. The expression of GFAP and UCH-L1 was significantly higher in the serum-derived exosomes from MMD patients compared with the healthy controls (P <0.05). Compared to the blank and control exosome group, serum-derived exosomes from MMD significantly suppress cellular vitality and promote apoptosis of SH-SY5Y cells, while the use of LDN-91946, a specific inhibitor of UCH-L1, could reverse the effects induced by serum-derived exosomes from MMD. Conclusion. UCH-L1 inhibitor could reverse MMD-induced inhibition of SH-SY5Y cell viability and promotion of apoptosis. UCH-L1 may be a therapeutic target for the treatment of nerve damage caused by MMD.